Analysis of Body Composition and Pain Intensity in Women with Chronic Pelvic Pain Secondary to Endometriosis - Silva, Joyce Beatriz da; Gurian, Maria Beatriz Ferreira; Nonino, Carla Barbosa; Poli-Neto, Omero Benedito; Nogueira, Antonio Alberto; Reis, Francisco José Candido dos; Silva, Júlio Rosa-e-Silva (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2020)
Objective To determine the average body composition (percentage of body fat), the anthropometric markers, and the intensity of clinical pain in women with a clinical diagnosis of chronic pelvic pain (CPP) secondary to endometriosis.Methods A case-control study performed with 91 women, 46 of whom with CPP secondary to endometriosis and 45 of whom with CPP secondary to other causes. They underwent an evaluation of the anthropometric parameters by means of the body mass index (BMI), the perimeters (waist, abdomen, hip), and the percentage of body fat (%BF), which were assessed on a body composition monitor by bioimpedance; the intensity of the clinical pain was evaluated using the visual analog scale (VAS), and the symptoms of anxiety and depression, using the hospital's anxiety and depression scale (HAD).Results The groups did not differ in terms of mean age, BMI, %BF or regarding the available waist-to-hip ratio (WHR). The mean intensity of the clinical pain by the VAS was of 7.2 ± 2.06 in the group with CPP secondary to endometriosis, and of 5.93 ± 2.64 in the group with CPP secondary to other causes (p = 0.03), revealing significant differences between the groups.Conclusion We concluded that, despite the difference in the pain score assessed between the two groups, there was no difference regarding body composition and anthropometry.
Keywords: chronic pelvic pain; fat percentage; pain intensity; anxiety; depression